Analisis Pengendalian Kualitas Proses Produksi Jenang Apel Dengan Metode Statistical Process Control (SPC) Untuk Menurunkan Tingkat Kerusakan Produk (Studi di CV. Bagus Agriseta Mandiri Batu) - Abdullah Faiq; Nur Hajati; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis research was conducted at CV. Bagus Agriseta Mandiri Batu. The purpose of this study was to find out how to use Statistical Process Control (SPC) to reduce the level of damage to apple jenang production on CV. Bagus Agriseta Mandiri Batu. This variable uses quality control, statistical process control (SPC), and product damage. Data collection methods using literature study and documentation. The sample used is the data of the number of production and the number of defects in May 2018. The data analysis uses check sheets, histograms, p control maps, and pareto diagrams. The Statistical Process Control (SPC) method to control the quality of apple jenang production shows that there is still a production defect which is shown on the control chart that there is a point that is outside the control limit. The types of production defects are mostly caused by dirty (34.38%), and water contamination by (25%).Keywords: Quality Control, Statistical Process Control, Product Damage